Analgesic Effect of Ultrasound-Guided Anterior Quadratus Lumborum Block at the L2 Level in Patients Undergoing Laparoscopic Partial Nephrectomy: A Single-Center, Randomized Controlled Trial - Ying He; Mingying Huang; Qiangui Zhong; Huijuan Ni; Zenggui Yu; Xinjian Zhang (Pain Research and Management)
Objectives. This study aimed to evaluate the effect of ultrasound-guided anterior quadratus lumborum block (QLB) at the L2 level in patients undergoing laparoscopic partial nephrectomy. Methods. Patients who were 18–70 years old with an American Society of Anesthesiologists (ASA) physical status of 1-2 and were scheduled for elective laparoscopic partial nephrectomy were recruited into the cluster randomized controlled trial. Sixty-three patients were randomly allocated to receive QLB (group Q, n = 32) or no block (group C, n = 31). The patients were not masked to the group allocations. The postoperative follower was blinded to the group allocations. All patients received total intravenous anesthesia, the same multimodal analgesic regimen, and rescue analgesia when needed. The primary outcome was perioperative cumulative sufentanil consumption. Results. 30 patients in group Q and 29 patients in group C were included in the statistical analysis. Block-related complications were not found in this study. Sufentanil consumption during the perioperative period (155.41 [19.58] vs 119.37 [12.41] μg, p < 0.001) and sufentanil dosage during surgery and 0–6 h, 6–12 h, and 12–24 h after surgery were lower in group Q than in group C, while 24–48 h after surgery was similar between both groups. The median sensory blockade area in group Q was T9-L1. Comparison of invasive blood pressure (BP) and heart rate (HR) before and after skin incision in group C was statistically significant, but there was no significant difference in group Q. Both at rest and during activity, numerical rating scale (NRS) scores and the incidence of rescue analgesia were lower in group Q at any time point after surgery. The incidences of postoperative nausea and vomiting (PONV), time from postoperative to discharge, postoperative recovery quality, or anesthesia satisfaction were similar between the two groups. Conclusions. Anterior QLB at the L2 level can reduce the perioperative dosage of sufentanil and the degree of postoperative pain in patients undergoing laparoscopic partial nephrectomy, but it did not improve postoperative recovery quality and anesthesia satisfaction.